Outline of the Method of an Aircraft Missile Homing System's Quality Estimation - Andrzej SKOMRA (Problemy Mechatroniki)
Quality of the missile homing system can be determined by the homing accuracy in stochastic way through determination of the expected value and variance of the final miss distance. The paper presents description of a method of distribution of current miss distance between the missile and the target using a random variable’s characteristic function. With a view to obtain an expression of miss distance, the author uses a formula describing angular velocity of the line of sight which was the solution of linearized simultaneous equations describing kinematic connections between missile and target together with proportional navigation guidance law.